Clinical and echocardiographic outcomes of transcatheter mitral valve repair in atrial functional mitral regurgitation. (15th December 2021) - Benito-González, Tomás; Carrasco-Chinchilla, Fernando; Estévez-Loureiro, Rodrigo; Pascual, Isaac; Arzamendi, Dabit; Garrote-Coloma, Carmen; Nombela-Franco, Luis; Pan, Manuel; Serrador, Ana; Freixa, Xavier; Cid Alvarez, Ana Belén; Hernández Antolín, Rosa Ana; et al.
Abstract: Background: Isolated atrial fibrillation can cause mitral regurgitation (MR) in patients with normal left ventricular systolic function and no organic disease of the mitral valve. Little information is available regarding outcomes of Mitraclip in patients with atrial functional mitral regurgitation (AFMR). We aimed to evaluate 12-month clinical and echocardiographic outcomes of transcatheter mitral valve repair (TMVR) with MitraClip in patients with AFMR compared to those with ventricular functional or degenerative/mixed MR. Methods: Registry-based analysis of all consecutive patients who underwent TMVR and were included in the Spanish Registry of Mitraclip. Changes in MR and NYHA functional class, and a combined endpoint including all-cause mortality and hospitalizations due to heart failure were the main outcomes. Results: Overall, 1074 (69.1% male, 73.3 ± 10.2 years-old) patients were analyzed in this report. 48 patients (4.5%) presented AFMR. AFMR was significantly reduced after TMVR, with a procedural success rate of 91.7%, and this reduction persisted at 12-month ( p  < 0.001). Patients with AFMR showed a significant functional improvement at 6- and 12-month follow-up in our series (baseline: NYHA III 70.8% IV 18.8% vs. 1-year: NYHA III 21.7% IV 0%; p < 0.001). The probability of survival free of readmission for heart failure and all-cause mortality within the first year after TMVR was 74.9%. Procedural and clinical outcomes, as well as recurrent rates of MR were similar acutely and at 1-year compared to other etiologies. Conclusion: TMVR in patients with AFMR showed no significant differences compared to ventricular functional or degenerative/mixed MR regarding MR reduction or clinical outcomes. Highlights: Only 4.5% of our cohort fulfilled criteria for AFMR Patients with AFMR showed a significant functional improvement at 6- and 12-month follow-up in our series. The probability of survival free of readmission for heart failure and all-cause mortality within the first year after TMVR was 74.9%. Procedural and clinical outcomes, as well as recurrent rates of MR were similar acutely and at 1-year compared to other etiologies of MR